(3GdJMbjb GdGHJOGFj aj bGfhf CUhd GdeMGceGJ GdLRGFjI (B:s (3OQGSI ebGQfI (B= Primary investigation in penal procedure principles law : a comparative study /s - (3GdLhNOGQ, MSfs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jJMOK GdcJGH Yf GdJMbjb GdGHJOGFj aj bGfhf CUhd GdeMGceGJ GdLRGFjI MjK bO fTCJ eQMdI GdJMbjb GdEHJOGFj ceQMdI hSWi Jdj GdHMK GdChdj hJegO ddeMGceI aj Xd (B((3fXGe GdJfbjH hGdJMQj(B) (3MjK jbhe GdeMbb HOhQ EjLGHj haGYd aj GdJfbjH Yf GdCOdI hLeYgG HgOa GdcTa Yf GdMbjbI haj MjK dG jYJQa (B((3GdfXGe GdEJgGej(B) (3HgPg GdeQMdI ajJQc egeI LeY GdCOdI ddNUhe aj GdOYhi jJJchf GdcJGH ef NeSI CHhGH GdHGH GdChd GdbhGYO GdYGeI aj GdJMbjb GdEHJOGFj hGdHGH GdKGfj eYGedGJ GdJMbjb GdNGUI HGdJfbjH Yf GdCOdI hGdHGH GdKGdK GdeYGedGJ GdEMJjGWjI ERGA GdeOYi Ydjg hGdHGH GdQGHY JUQa GdeOYj GdYGe GdeMbb aj GdJMbjb GdEHJOGFj hGdHGH GdNGeS OhQ GdfGFH GdYGe aj GdJMbjb GdEHJOGFj(B.s
(3HHdjhLQGajI (B: (3UaMI (B625-641. s
Keywords: (3GdJMbjb GdLfGFjs; (3bGfhf GdELQGAGJ GdLfGFjIs; (3GdeMGceGJ GdLfGFjIs